2011
DOI: 10.1158/1078-0432.ccr-10-2412
|View full text |Cite
|
Sign up to set email alerts
|

Stathmin Overexpression Identifies High-Risk Patients and Lymph Node Metastasis in Endometrial Cancer

Abstract: Purpose: Overexpression of the oncogen Stathmin has been linked to aggressive endometrial carcinoma and a potential for PI3Kinase inhibitors in this disease. We wanted to validate the prognostic value of Stathmin expression in a large prospective multicenter setting. As lymph node sampling is part of current surgical staging, we also aimed to test if Stathmin expression in endometrial curettage specimens could predict lymph node metastasis.Experimental Design: A total of 1,076 endometrial cancer patients have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
113
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 114 publications
(119 citation statements)
references
References 40 publications
5
113
1
Order By: Relevance
“…In total, 641 patients with endometrial cancer were consecutively and prospectively included in our database from May 2001 to November 2011 and treated at the department of gynecology and obstetrics, Haukeland University Hospital, Bergen, Norway. Clinicopathological data including age at diagnosis, FIGO 2009 stage, 15 histological subtype, grade and treatment were recorded as previously reported 16 and formalin-fixed paraffin-embedded tumor tissue was collected from all patients. Patients were routinely subjected to hysterectomy and bilateral salpingooophorectomy after obtaining a histological diagnosis of endometrial cancer, unless surgery was contra-indicated due to severe co-morbidity.…”
Section: Patient Seriesmentioning
confidence: 99%
“…In total, 641 patients with endometrial cancer were consecutively and prospectively included in our database from May 2001 to November 2011 and treated at the department of gynecology and obstetrics, Haukeland University Hospital, Bergen, Norway. Clinicopathological data including age at diagnosis, FIGO 2009 stage, 15 histological subtype, grade and treatment were recorded as previously reported 16 and formalin-fixed paraffin-embedded tumor tissue was collected from all patients. Patients were routinely subjected to hysterectomy and bilateral salpingooophorectomy after obtaining a histological diagnosis of endometrial cancer, unless surgery was contra-indicated due to severe co-morbidity.…”
Section: Patient Seriesmentioning
confidence: 99%
“…Moreover, upregulated stathmin has been shown to be extensively correlated with poor survival. In one particular analysis involving 1,076 endometrial cancer specimens, stathmin overexpression was significantly associated with poor survival of the patients and with nodal metastasis [18].…”
Section: Relevance Of Stmn1 To Cancermentioning
confidence: 99%
“…The incidence of endometrial cancer is increasing worldwide. Several biomarkers have shown associations with clinical characteristics and prognosis in endometrial cancer (1)(2)(3)(4)(5)(6), but currently none are implemented in routine clinical practice. There is a need for identification of new biomarkers improving our understanding, diagnosis, and follow-up of endometrial cancer (7).…”
Section: Introductionmentioning
confidence: 99%